The Influence Of Board Knowledge And Political Background On Regional Financial Oversight With Community Participation And Public Policy Transparency As Moderating Variables - Liza Hanim; Biana Adha Inapty (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to examine how the knowledge of council members regarding budgets and political backgrounds affects regional financial supervision, taking into account the moderating effects of community participation and public policy transparency. The method used in this research is quantitative, with 50 samples collected directly by the researcher. The results indicate that council knowledge affects financial supervision, political background also influences financial supervision, community participation serves as a moderator in financial supervision, while public policy transparency also plays a moderating role in the same context.